Population pharmacokinetics of high‐dose methotrexate in Chinese pediatric patients with medulloblastoma. (12th February 2020) - Shi, Zheng‐yuan; Liu, Ya‐ou; Gu, Hong‐yan; Xu, Xi‐qiao; Yan, Can; Yang, Xin‐yu; Yan, Dan
Abstract: Methotrexate (MTX) pharmacokinetics has substantial inter‐individual variability and toxicity. In children with medulloblastoma treated with high‐dose methotrexate (HD‐MTX), the pharmacokinetic properties of methotrexate have not been established. A total of 660 serum samples from 105 pediatric patients with medulloblastoma were included in a population pharmacokinetic (PPK) analysis of methotrexate by using the nonlinear mixed‐effects modeling method. The basic one‐compartment population pharmacokinetic model was established by NONMEM software and the first‐order conditional estimation (FOCE) method, and the final covariate model was obtained by the stepwise regression method. Weight (WT), creatinine clearance (CrCL), and whether the treatment was combined with dexamethasone (DEX) were covariates that had significant effects on the clearance rate (CL) of the model. The pharmacokinetic equation of CL in the final covariate model was as follows: CLi = 9.23× (1 + 0.0005× (θCrCL ‐105.78)) × (1 + 0.0017× (θWT ‐16)) × e ηcl, i (L/h), IF (θDEX ) CLi = 1.19× CLi (L/h). The estimation accuracy of all pharmacokinetic parameters were acceptable (relative standard error < 14.74%). The goodness‐of‐fit diagram and bootstrap tests indicated that the final PPK model was stable with acceptable predictive ability. The PPK model may be useful for determining personalized medication levels in pediatric medulloblastoma patients undergoing HD‐MTX therapy.